EC Bananarama 1992: the sequel: the EC Commission proposal - Borrell, Brent (IBRD Washington, D.C.US, 1992)
Analyses world banana trade to reflect the market in 1993. Evaluates the implications of the Commission's proposal alongside existing and alternative policies. Concludes that the EC proposal for a unified banana policy is just another way of replacing existing distortionary national policies with an almost equally distortionary single policy and market.